2005
DOI: 10.1021/jp0502813
|View full text |Cite
|
Sign up to set email alerts
|

A Vacuum Ultraviolet Photoionization Mass Spectrometric Study of Acetone

Abstract: The photoionization and dissociative photoionization of acetone have been studied at the photon energy range of 8-20 eV. Photoionization efficiency spectra for ions CH3COCH3+, CH3+, C2H3+, C3H3+, C3H5+, CH(2-)CO+, CH3CO+, C3H4O+, and CH3COCH2+ have been measured. In addition, the energetics of the dissociative photoionization has been examined by ab initio Gaussian-3 (G3) calculations. The computational results are useful in establishing the dissociation channels near the ionization thresholds. With the help o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 27 publications
5
42
0
Order By: Relevance
“…The photoionization of acetone and dissociation of the acetone cation, CH 3 COCH 3 + , have been reported previously by several groups [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The unimolecular dissociation of acetone cation has been investigated using photoionization efficiency and photoelectron-photoion coincidence (PEPICO) spectra [16][17][18][19][20]22] and various theories [27][28][29]. The following dissociation channels have been observed in the low internal energy region of the acetone cation: Cant et al [16] reported that: (a) at 0-0.3 eV above the ionization threshold (9.7 eV) of acetone only the parent ions were observed; (b) CH 3 CO + appeared at 10.3 eV; (c) the CH 3 + product channel was initiated at approximately 13 eV; (d) at the ionization energy to the first excited state of acetone cation, ~12 eV, some parent ions were observed along with dominant CH 3 CO + fragments; and (e) the average kinetic energy releases of CH 3 CO + and CH 3 + were found to vary linearly with the internal energy of the acetone cation in the low energy region.…”
supporting
confidence: 52%
See 3 more Smart Citations
“…The photoionization of acetone and dissociation of the acetone cation, CH 3 COCH 3 + , have been reported previously by several groups [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The unimolecular dissociation of acetone cation has been investigated using photoionization efficiency and photoelectron-photoion coincidence (PEPICO) spectra [16][17][18][19][20]22] and various theories [27][28][29]. The following dissociation channels have been observed in the low internal energy region of the acetone cation: Cant et al [16] reported that: (a) at 0-0.3 eV above the ionization threshold (9.7 eV) of acetone only the parent ions were observed; (b) CH 3 CO + appeared at 10.3 eV; (c) the CH 3 + product channel was initiated at approximately 13 eV; (d) at the ionization energy to the first excited state of acetone cation, ~12 eV, some parent ions were observed along with dominant CH 3 CO + fragments; and (e) the average kinetic energy releases of CH 3 CO + and CH 3 + were found to vary linearly with the internal energy of the acetone cation in the low energy region.…”
supporting
confidence: 52%
“…The vibra-*Corresponding author (email: zxf7002@mail.ahnu.edu.cn) tional assignments in the 3p Rydberg state were deduced from polarization-selected two-and three-photon resonance enhanced multiphoton ionization (REMPI) spectroscopy [7,8,10,12,14,15]. The photoionization of acetone and dissociation of the acetone cation, CH 3 COCH 3 + , have been reported previously by several groups [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The unimolecular dissociation of acetone cation has been investigated using photoionization efficiency and photoelectron-photoion coincidence (PEPICO) spectra [16][17][18][19][20]22] and various theories [27][28][29].…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…6 Appearance potential of the methyl radical loss from the acetone cation (CH 3 COCH 3 · + → CH 3 CO + + CH 3 ·) is 10.563 eV. 6 Recently, rich dissociation processes of the acetone cation in the vacuum ultraviolet (VUV) energy region have been investigated by threshold photoelectron photoion coincidence (TPEPICO) spectroscopy, 6 VUV photoabsorption and ionization using synchrotron radiation, 7,8 and electron impact ionization. 9 The dissociative ionization of acetone above the threshold energy of the methyl radical loss from the acetone cation was also observed in the previous multiphoton ionization (MPI) experiments.…”
Section: Introductionmentioning
confidence: 99%